2015
DOI: 10.4172/2471-2663.1000106
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Citronella Essential Oil on Antimicro bial Drug Resistant Bacteria from Veterinary Clinical Cases

Abstract: Study on citronella essential oil (CEO) sensitivity of 217 microbial strains of 65 species, isolated from animals with different disease conditions, revealed that citronella oil inhibited growth of only 10.6% strains. CEO inhibited Candida but of no Aspergillus strain. CEO inhibited 22 of 211 bacterial strains. Ampicillin was the least effective antibiotic but inhibited 41.2% bacterial strains. Gram positive bacteria (GPBs) were 4.5 more sensitive (p, 0.0006) to CEO than Gram negative bacteria (GNBs). More GNB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
3
2
1
Order By: Relevance
“…Difference in sensitivity to TTO among strains of different origin observed in the present study further proved the same fact that origin of strains might be an important determinant for determining its sensitivity to TTO as reported earlier for other herbal drugs [21,[24][25][26][27][28][29]. Similar sensitivity pattern of bacteria of mithun origin for other antimicrobials as to TTO, i.e., more commonly sensitive to other antimicrobials than strains of other origin further suggested the similar mechanism of emergence of resistance to antibiotics and TTO or probably for other herbal drugs too [29].…”
Section: Discussionsupporting
confidence: 90%
“…Difference in sensitivity to TTO among strains of different origin observed in the present study further proved the same fact that origin of strains might be an important determinant for determining its sensitivity to TTO as reported earlier for other herbal drugs [21,[24][25][26][27][28][29]. Similar sensitivity pattern of bacteria of mithun origin for other antimicrobials as to TTO, i.e., more commonly sensitive to other antimicrobials than strains of other origin further suggested the similar mechanism of emergence of resistance to antibiotics and TTO or probably for other herbal drugs too [29].…”
Section: Discussionsupporting
confidence: 90%
“…Though A. conyzoides is usually not consumed by animals but in scarcity, it may be. Similar views have also been expressed earlier for higher resistance in bacterial isolates from such kinds of animals for A. vulgaris, lemon grass and citronella oil [21,22,[24][25][26].…”
Section: Discussionsupporting
confidence: 74%
“…In the present study, the most sensitive strains to ACME belonged to oxidase positive GPBs (62.5%) followed by oxidase negative GPBs (40.8%), oxidase positive GNBs (27.4%) and oxidase negative GNBs (4.9%). The role of oxidase production ability might be important in herbal drug resistance, similar observation have been made earlier with lemongrass oil [24], Artemesia vulgaris oil [25,26], geranium oil [21] and citronella oil [22].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The study showed that the incorporation of both essential oils exhibited excellent antibacterial properties against both Gram-negative (Escherichia coli) and Gram-positive (Staphylococcus aureus) bacteria. The inhibition activities were triggered by the presence of a major constituent in both essential oils that were identified as p-menthone and menthol and citronellal and citronellol for peppermint and citronella essential oils, respectively [55,56]. While, Martucci et al [57] observed the antimicrobial activity of oregano and lavender essential oils incorporated into gelatin film that were tested against Escherichia coli and Staphylococcus aureus.…”
Section: Plant-derived Antimicrobial Agentmentioning
confidence: 99%